321 Effect of maturation on knee extensor and flexor strength in male and female adolescent athletes. (3rd March 2020) - Peek, Kerry; Ford, Kevin; Myer, Gregory; Hewett, Timothy; Pappas, Evangelos
Abstract : Background: Knee extensor and flexor strength are associated with injury risk, including rupture of the anterior cruciate ligament. However, the longitudinal changes in lower extremity strength with maturation have been under-investigated. Objective: To investigate the longitudinal changes of knee extension and flexion strength associated with maturation Design: The pubertal status [pre-pubertal, pubertal, and post-pubertal] was determined with the modified Pubertal Maturation Observation Scale questionnaire. After a warm-up of five submaximal repetitions, participants were tested for concentric peak isokinetic strength for knee extension and flexion at 300°/s. Setting: Laboratory. Patients (or Participants): Males and females participating in high school sports who were measured longitudinally in at least two different pubertal stages (N=257, 208 females, 18 excluded due to knee injury). Interventions (or assessment of risk factors): N/A Main outcome measurements: Peak knee extension and flexion isokinetic torque was measured across 10 repetitions and normalized to body weight. Separate linear mixed models were used for the right and left side to test for the effect of pubertal stage, sex and their interaction. Results: Significant interactions were identified indicating a different maturational effect on knee muscle strength for males and females, particularly between pre-pubertal and pubertal stages where males demonstrated higher knee extension increases than females (+12% vs. +5% on right, +11% vs. +7% on left, p<0.001) while for knee flexion males demonstrated increased while females demonstrated decreased flexor strength (+4% vs. -1% on right, p=0.03 and +3 vs. -3% on left, p=0.009). Conclusions: The findings of this study support a differential effect of maturation on important knee strength outcomes that may have implications for the higher rates of knee injury in females as they mature. Interventions to strengthen the knee flexors should target females at the beginning of puberty and emphasized in injury reduction programs aimed at young athletes of both sexes.